Evaluation of the use of wastewater treated with Lemnas minor in bean yield and nutrition - dos Santos Lima, Rafael [UNESP]; Cavalcante, Valéria Santos; Garcia, João Batista Ferraz [UNESP]; Filho, Helio Grassi [UNESP]; de Morais, Leandro Cardoso [UNESP]; Tonetti, Adriano Luiz (Universidade Estadual de Londrina, 2022)
Irrigation with wastewater can reduce the demand for drinking water, reduce its disposal into water bodies and provide nutrients for agricultural crops. Thus, the objective of the present study was to evaluate the irrigation using wastewater with and without polishing by Lemnaceae macrophytes on the production and nutrition of common bean plants. Common bean (IPR Andorinha) was cultivated in a greenhouse in a completely randomized experimental design, with three treatments (T1= public-supply water (PSW); T2 = wastewater without polishing (WWNP) and T3 = wastewater with polishing by macrophytes (WWPL)). The highest contents of macronutrients and micronutrients in the common bean crop irrigated with PSW, WWPL and WWNP were found in the following order: K > Ca > N > Mg > S > P and Fe > B > Mn > Zn > Cu. Compared to PSW, wastewater promoted higher green color index (17.1%), number of pods (24%), grain yield (28%), fresh matter (33%) and dry matter (42%). Wastewater with and without polishing provides adequate nutrition and dry matter production, and wastewater with polishing increased the number of grains and grain yield in common bean.
Avaliação do uso de águas residuárias tratadas com Lemnas minor na produtividade e nutrição do feijoeiro
Keywords: Aquatic macrophytes; Phaseolus vulgaris; Reuse water